Combinatorial effect of Gallic acid and Catechin on some biochemical and pro-inflammatory markers in CCl4-mediated hepatic damage in rats - Kelly Oriakhi; Kissinger O. Orumwensodia (Elsevier, 2021)
The present study investigated the combinatorial effect of gallic acid and catechin (GC) on some biochemical and inflammatory parameters in CCl4-mediated hepatic damage to rats. Male Wistar rats were distributed equally into five groups. Group A (control) received distilled water orally and olive oil intraperitoneally (ip), group B rats were intoxicated with CCl4 {1.25 ml/kg in olive oil, ip) only, while Groups C, D and E were induced with CCl4, thereafter they were administered 50 mg/kg body weight of silymarin, combined dose of gallic acid and catechin (50 and 100 mg/kg bw, 1:1) for 7 days respectively. After 7 days of treatment, the rats were sacrificed, and the fasting blood sample was collected by cardiac puncture for biochemical analyses. Findings from our results show that there were significant increases (p ˂ 0.05) in serum hepatic enzyme markers (ALT, AST, ALP, and GGT activities), bilirubin, albumin, and malondialdehyde (MDA) concentrations, but a significant decrease in GSH, SOD and CAT activities. It was also observed that the antioxidant genes coding for SOD and CAT were down-regulated or suppressed, while the inflammatory cytokines (IL-1B, IL-6, COX 2, and TNF α) were activated in rats intoxicated with CCl4 when compared to the control group. Administration of the combined dose of GC and silymarin drug attenuated the toxic insult of CCl4 at the biochemical and molecular levels. Our findings confirm that a combination of gallic acid and catechin may have exhibited a synergistic hepatoprotective activity against CCl4 induced liver damage.